The Students' Learning Difficulties In Learning English During Pandemic Era At SMP Negeri 1 Parepare - Risdayanti (La Parole : Journal of Language Teaching and Pedagogy, 2020)
Analysis is an investigation of an event to find out the actual situation during the COVID-19 pandemic in a situation where large-scale social restrictions (PSBB) were imposed. The purpose of this research is to find out that objective of the research the students' difficulties in learning English and the factors that influence these difficulties at SMP NEGERI 1 Parepare.This type of research is a descriptive type of research using a qualitative approach which is carried out to find the various difficulties experienced by students in learning English at Smp Negeri 1 Parepare. This descriptive study is more focused on collecting data to describe the actual situation that occurs in the field using questionnaires and interviews measured by a Likert scale. Based on the results obtained through the distribution of questionnaires containing statements about the difficulties of learning English during the COVID-19 pandemic, which amounted to sixteen statements to ten students and ten question addressed to one English teacher at Smp Negeri 1 Parepare. Two factors are obtained, namely internal factors, namely learning abilities and external factors, namely the lack of costs and communication tools used by students.